A composite positive electrode material and preparation method thereof and positive electrode sheet

By forming a polyaniline coating on the positive electrode materials of sodium ion batteries and lithium ion batteries, the problem of insufficient conductivity of the positive electrode materials is solved, the energy density and charging and discharge efficiency of the battery are improved, and more stable battery performance is achieved.

CN119764371APending Publication Date: 2025-04-04HUNAN LIFANG NEW ENERGY SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411790805.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The current sodium-ion batteries and lithium-ion batteries have poor conductivity, resulting in low-rate performance and low energy density of the batteries.

Method used

A composite positive electrode material is used, which consists of a positive electrode material matrix and a polyaniline coating layer coated on the surface of the matrix. Through a polymer rich in phenolic hydroxyl groups, aniline is induced to polymerize on the surface of the positive electrode material matrix to form a uniform and firm polyaniline coating layer.

Benefits of technology

It improves the conductivity and electrochemical performance of the positive electrode material, enhances the energy density and charge and discharge efficiency of the battery, stabilizes the battery structure, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764371A_ABST
    Figure CN119764371A_ABST
Patent Text Reader

Abstract

The present invention discloses a composite positive electrode material and a preparation method thereof and a positive electrode sheet. The composite positive electrode material comprises a positive electrode material matrix and a polyaniline coating layer coated on the surface of the matrix; the positive electrode material matrix is ​​connected to the polyaniline coating layer through a polymer, and each structural unit in the polymer comprises at least two phenolic hydroxyl functional groups. Compared with the prior art, the positive electrode material matrix and the polyaniline coating layer of the composite positive electrode material of the present invention are connected by a polymer rich in phenolic hydroxyl groups, and the polymer rich in phenolic hydroxyl groups on the surface of the positive electrode material matrix induces aniline to polymerize on the surface of the positive electrode material matrix to form a uniform and firm polyaniline coating layer, thereby obtaining a composite positive electrode material with high conductivity and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite positive electrode material and a preparation method thereof and a positive electrode sheet. Background Art

[0002] Secondary batteries have many advantages such as greenness, high safety, high electrochemical potential, design flexibility, high energy density and recyclability. They are used as one of the ideal substitutes for traditional chemical energy and are widely used in many industries such as information communication and new energy vehicles. Lithium-ion batteries and sodium-ion batteries are the most widely used types of secondary batteries. Lithium-sodium-ion batteries have the same structure and working principle and are both rocking chair batteries. They are usually made of positive active materials, negative active materials, electrolytes, separators and positive and negative current collectors.

[0003] Among them, the positive electrode active material is the most critical link. The conductivity of the positive electrode material of the sodium ion battery is relatively poor, and the radius is larger, which inevitably brings greater resistance to deintercalation, resulting in low rate performance and low energy density of the sodium ion battery. Similar to it, lithium iron phosphate, as the main positive electrode material of lithium battery, has the advantages of low price and stable structure. However, due to its one-dimensional conductive channel characteristics, its ion diffusion and electronic conductivity are significantly lower than other lithium ion positive electrode materials, which greatly limits its application field.

[0004] In view of the above-mentioned defects existing in the current positive electrode materials, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0005] The purpose of the present invention is to provide a composite positive electrode material with high electrical conductivity and excellent electrochemical performance.

[0006] In order to achieve this object, the present invention provides the following scheme:

[0007] A composite positive electrode material, comprising a positive electrode material substrate and a polyaniline coating layer coated on the surface of the substrate;

[0008] The positive electrode material matrix is ​​connected to the polyaniline coating layer via a polymer, and each structural unit in the polymer includes at least two phenolic hydroxyl functional groups.

[0009] Preferably, the polymer is one of polydopamine and polytannic acid.

[0010] Preferably, the positive electrode material matrix includes one of a polyanion sodium ion battery positive electrode material and a lithium ion battery positive electrode material, wherein the polyanion sodium ion battery positive electrode material includes one of sodium iron phosphate, sodium iron sulfate and sodium vanadium phosphate; and the lithium ion battery positive electrode material includes one of lithium iron phosphate and lithium iron manganese phosphate.

[0011] Preferably, the conductivity of the composite positive electrode material is 10 -4 ~10 -6 S / cm.

[0012] The present invention also provides a method for preparing a composite positive electrode material, comprising the following steps:

[0013] Step 1: Add polymer monomers to the Tris solution, then add the cathode material matrix, and stir for 3 to 4 hours to obtain a mixed solution A; wherein the pH of the Tris solution is 8 to 9, and the concentration is 0.1 mol / L;

[0014] Step 2: Filter the mixed solution A, rinse the filter residue with deionized water and anhydrous ethanol, and dry at 70-90° C. for 7-9 hours to obtain the positive electrode material to be coated;

[0015] Step 3: preparing a coating layer solution, wherein the concentration of aniline is 90-160 mM / L, and the concentration of phytic acid is 9-32 mM / L; preparing a 240-960 mM / L ammonium persulfate aqueous solution;

[0016] Step 4: adding the positive electrode material to be coated into the coating layer solution, dropping the ammonium persulfate solution, and continuously stirring for 6 to 10 hours to obtain a mixed solution B;

[0017] Step 5: Filter the mixed solution B, rinse the filter residue with deionized water and anhydrous ethanol, and dry it at 70-90° C. for 6-10 hours to obtain a composite positive electrode material.

[0018] Preferably, in step 1, the polymer monomer is one of dopamine hydrochloride and tannic acid; and the concentration of the polymer monomer in the mixed solution A is 1.2 mg / mL.

[0019] Preferably, in the step 1, the molar mass ratio of the polymer monomer to the positive electrode material matrix is ​​0.2% to 1.6%.

[0020] Preferably, in step three, the molar mass ratio of the aniline to the positive electrode material matrix is ​​3.0% to 5.0%; and in the coating layer solution, the molar mass ratio of the aniline to the phytic acid is 5 to 10:1; in addition, the molar mass ratio of the aniline to the ammonium persulfate is 1:0.5 to 2.

[0021] Preferably, in step 4, the stirring condition is an ice bath at a temperature of 0 to 3°C.

[0022] The present invention also provides a positive electrode sheet, comprising a positive electrode material, a conductive agent and a binder, wherein the positive electrode material is the composite positive electrode material mentioned above.

[0023] The present invention also provides a secondary battery, comprising a diaphragm, a negative electrode sheet, an electrolyte, a battery casing and the positive electrode sheet mentioned above.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the positive electrode material matrix and the polyaniline coating layer of the composite positive electrode material of the present invention are connected by a polymer rich in phenolic hydroxyl groups, and the polymer rich in phenolic hydroxyl groups on the surface of the positive electrode material matrix induces aniline to polymerize on the surface of the positive electrode material matrix to form a uniform and firm polyaniline coating layer, thereby obtaining a composite positive electrode material with high conductivity and excellent electrochemical properties; wherein polyaniline is a highly conductive polymer material, and the polyaniline coating layer can improve the conductivity of the positive electrode material matrix, and can also stabilize the structure of the composite positive electrode material, reduce the phase change stress generated by the embedding and extraction of metal ions during the charge and discharge process, and help maintain the integrity and performance stability of the composite positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the structure of a composite positive electrode material according to an embodiment of the present invention;

[0026] Figure 2 The charging curve diagram of the lithium ion battery of Examples 1 to 3 and Comparative Example 1;

[0027] Figure 3 The EIS test curves of the lithium ion batteries of Examples 1 to 3 and Comparative Example 1 are shown;

[0028] Figure 4 The figure is a charge and discharge curve diagram of the sodium ion battery of Examples 4 and 5 and Comparative Example 2.

[0029] Among them, 1. positive electrode material matrix; 2. polymer; 3. polyaniline coating layer. DETAILED DESCRIPTION

[0030] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] According to a first aspect of the present invention, there is provided a composite positive electrode material, comprising a positive electrode material substrate and a polyaniline coating layer coated on the surface of the substrate;

[0032] The positive electrode material matrix is ​​connected with the polyaniline coating layer through a polymer, and the polymer includes at least a plurality of phenolic hydroxyl functional groups.

[0033] The positive electrode material matrix and the polyaniline coating layer of the composite positive electrode material of the present invention are connected by a polymer rich in phenolic hydroxyl groups. The polymer rich in phenolic hydroxyl groups on the surface of the positive electrode material matrix induces aniline to polymerize on the surface of the positive electrode material matrix to form a uniform and firm polyaniline coating layer, thereby obtaining a composite positive electrode material with high conductivity and excellent electrochemical performance.

[0034] Polyaniline is a highly conductive polymer material that can improve the conductivity of the positive electrode material matrix, stabilize the structure of the positive electrode material, reduce the phase change stress caused by the insertion and extraction of lithium ions during the charging and discharging process, and help maintain the integrity and performance stability of the positive electrode material.

[0035] In one embodiment according to the present invention, the polymer is polydopamine.

[0036] First, dopamine is oxidized and polymerized to polydopamine on the surface of the positive electrode material matrix in an alkaline aerobic environment. Polydopamine can provide an "anchor point" for the subsequent self-polymerization of conductive polyaniline, thereby forming a uniform and firm polyaniline coating layer, thereby obtaining a composite positive electrode material with high electrical conductivity and excellent electrochemical properties.

[0037] In one embodiment of the present invention, the positive electrode material matrix includes one of a polyanion type sodium ion battery positive electrode material and a lithium ion battery positive electrode material, wherein the polyanion type sodium ion battery positive electrode material includes one of sodium iron phosphate, sodium iron sulfate and sodium vanadium phosphate; the lithium ion battery positive electrode material includes one of lithium iron phosphate and lithium iron manganese phosphate. The conductivity of traditional positive electrode materials is poor, and the present invention improves the conductivity of these positive electrode materials by forming a polyaniline coating layer on the surface of the positive electrode material particles.

[0038] In one embodiment of the present invention, the conductivity of the composite positive electrode material is 10 -4 ~10 -6 S / cm. The low conductivity of the positive electrode material in the secondary battery will have a negative impact on the battery's performance, charge and discharge rate, polarization phenomenon, low temperature performance and life. The composite positive electrode material of the present invention improves the conductivity of the positive electrode material and has a positive impact on the performance, energy density, efficiency, stability, high and low temperature performance, design flexibility and safety of the secondary battery.

[0039] Specifically, the composite positive electrode material of the present invention can more effectively utilize active substances, reduce internal resistance and energy loss, and thus improve the energy density of the battery; lower internal resistance and energy loss means that the battery is more efficient during the charging and discharging process, and also improves the overall performance and service life of the battery.

[0040] In a second aspect of the present invention, a method for preparing a composite positive electrode material is also provided, comprising the following steps:

[0041] Step 1: Add polymer monomers to the Tris solution, then add the cathode material matrix, and stir for 3 to 4 hours to obtain a mixed solution A; wherein the pH of the Tris solution is 8 to 9, and the concentration is 0.1 mol / L;

[0042] Step 2: Filter the mixed solution A, rinse the filter residue with deionized water and anhydrous ethanol, and dry it at 70-90° C. for 7-9 hours to obtain the positive electrode material to be coated;

[0043] Step 3: prepare a coating solution, wherein the concentration of aniline is 90-160mM / L, for example, 90mM / L, 95mM / L, 100mM / L, 105mM / L, 110mM / L, 115mM / L, 120mM / L, 125mM / L, 130mM / L, 138mM / L, 140mM / L, 148mM / L, 150mM / L, 158mM / L, 160mM / L; within this range, the content of coated polyaniline is appropriate; if the concentration of aniline is too low, the coating layer will not be dense and uniform enough, and the improvement effect of kinetic performance will not be obvious; if the concentration of aniline is too high, the proportion of the main material will be reduced, showing a lower specific capacity.

[0044] The concentration of phytic acid is 9-32mM / L, for example, it can be 9mM / L, 11mM / L, 15mM / L, 18mM / L, 20mM / L, 22mM / L, 24mM / L, 26mM / L, 28mM / L, 30mM / L, 32mM / L; phytic acid is mainly used as a cross-linking agent and dopant. If the concentration is too high, it may cause polyaniline to agglomerate and fail to form a uniform coating layer; if the concentration is too low, the conductivity of polyaniline will be reduced, and the dynamic properties of the composite material cannot be effectively improved.

[0045] A 240-960 mM / L aqueous ammonium persulfate solution is prepared, for example, 240 mM / L, 300 mM / L, 400 mM / L, 500 mM / L, 600 mM / L, 700 mM / L, 800 mM / L, 900 mM / L, 960 mM / L; ammonium persulfate is used as an oxidant. If the concentration is too high, the conductive redox intermediates will be over-oxidized, the conjugated π bonds will be destroyed, and the intermediates will become insulators; if the concentration is too low, the product will not undergo sufficient oxidative polymerization reaction, and polyaniline with a low degree of polymerization will be obtained.

[0046] Step 4: Add the cathode material to be coated into the coating layer solution, dropwise add the ammonium persulfate solution, and continue stirring for 6 to 10 hours to obtain a mixed solution B;

[0047] Step 5: Filter the mixed solution B, rinse the filter residue with deionized water and anhydrous ethanol, and dry it at 70-90° C. for 6-10 hours to obtain a composite positive electrode material.

[0048] In one embodiment of the present invention, in step 1, the polymer monomer is one of dopamine hydrochloride and tannic acid; and the concentration of the polymer monomer in the mixed solution A is 1.2 mg / mL.

[0049] In one embodiment of the present invention, in step 1, the molar mass ratio of the polymer monomer to the cathode material matrix is ​​0.2% to 1.6%, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%. If the polymer monomer is too little, it is impossible to provide enough "anchor points" for the subsequent coating of the polyaniline coating layer, and thus it is impossible to form a uniform and firm polyaniline coating layer on the surface of the cathode material matrix, resulting in the inability to improve the conductivity and electrochemical performance of the cathode material.

[0050] In one embodiment of the present invention, in step three, the molar mass ratio of aniline to the positive electrode material matrix is ​​3.0% to 5.0%, for example, it can be 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%; if the aniline content is too low, the coating layer will not be dense and uniform enough, and the kinetic performance improvement effect will not be obvious. If the aniline content is too high, the proportion of the main material will be reduced, showing a lower specific capacity.

[0051] Furthermore, in the coating layer solution, the molar mass ratio of aniline to phytic acid is 5 to 10:1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1; aniline is in-situ self-polymerized on the surface of the cathode material matrix by protonic acid doping and ammonium persulfate oxidant to obtain a composite cathode material with a polyaniline coating layer. If the phytic acid content is too high, it may cause polyaniline to agglomerate and fail to form a uniform coating layer; if the content is too low, the conductivity of polyaniline will be reduced, and the dynamic performance of the composite material cannot be effectively improved.

[0052] In addition, the molar mass ratio of aniline to ammonium persulfate is 1:0.5-2, for example, 2:1, 1:1, 1:2, etc. Aniline is in situ self-polymerized on the surface of the cathode material matrix by protonic acid doping and ammonium persulfate oxidant to obtain a composite cathode material with a polyaniline coating layer.

[0053] In one embodiment of the present invention, in step 4, the stirring condition is an ice bath at a temperature of 0-3°C, for example, 0°C, 1°C, 2°C or 3°C.

[0054] In the third aspect of the present invention, a positive electrode sheet is also provided, comprising a positive electrode material, a conductive agent and a binder, wherein the positive electrode material is the composite positive electrode material mentioned above.

[0055] In a fourth aspect of the present invention, a secondary battery is provided, comprising a separator, a negative electrode sheet, an electrolyte, a battery casing and the positive electrode sheet mentioned above.

[0056] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0057] The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys. The negative electrode current collector is usually a structure or part for collecting current. The negative electrode current collector may be any material suitable for use as a negative electrode current collector for secondary batteries in the art. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.

[0058] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0059] The present invention will be further described below by means of specific examples.

[0060] Example 1

[0061] Preparation of composite cathode materials:

[0062] Step 1: Add 0.12 g of dopamine hydrochloride to 100 mL of Tris solution, then add 50 g of lithium iron phosphate, and stir at room temperature for 4 hours to obtain a mixed solution A; wherein the pH of the Tris solution is 8.5 and the concentration is 0.1 mol / L;

[0063] Step 2: Filter the mixed solution A, rinse the residue with deionized water and anhydrous ethanol for 5 times, and dry it at 80°C for 10 hours to obtain the positive electrode material to be coated;

[0064] Step 3: prepare 100 mL of coating solution, wherein the concentration of aniline is 95 mM / L and the concentration of phytic acid is 9.5 mM / L; prepare 20 mL of ammonium persulfate aqueous solution with a concentration of 240 mM / L;

[0065] Step 4: Add the cathode material to be coated into the coating layer solution, dropwise add the ammonium persulfate solution, and continue stirring for 8 hours to obtain a mixed solution B;

[0066] Step 5: Filter the mixed solution B, rinse the filter residue with deionized water and anhydrous ethanol for 5 times respectively, and dry it at 80° C. for 10 hours to obtain a composite positive electrode material.

[0067] Preparation of secondary batteries:

[0068] The negative electrode sheet, the positive electrode sheet and the separator are interlaced and wound and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is the above-mentioned composite positive electrode material.

[0069] Table 1 shows the data of Examples 1 to 9 and Comparative Examples 1 to 5, and the rest is the same as Example 1 and will not be described again.

[0070] Table 1

[0071]

[0072] Example 9

[0073] Different from Example 1, in this example, 0.12 g of tannic acid is added in step 1.

[0074] The rest are the same as in Example 1 and will not be described again.

[0075] Performance Testing:

[0076] The positive electrode sheets of Examples 1 to 9 and Comparative Examples 1 to 5 were tested for membrane internal resistance and conductivity, and the test results are shown in Table 2;

[0077] The secondary batteries of Examples 1 to 9 and Comparative Examples 1 to 5 were subjected to electrochemical performance tests. The test results are shown in Table 2. Figure 2 , Figure 3 and Figure 4 ;

[0078] Table 2

[0079] Group Gram capacity (mAh / g) Diaphragm internal resistance (Ω·cm) Electrical conductivity (S / cm) Example 1 140.7 45.6 <![CDATA[2.59·10 -2 ]]> Example 2 140.4 40.6 <![CDATA[2.46·10 -2 ]]> Example 3 140.5 38.9 <![CDATA[2.18·10 -2 ]]> Example 4 140.8 28.3 <![CDATA[3.53·10 -2 ]]> Example 5 141.8 23.6 <![CDATA[4.24·10 -2 ]]> Example 6 142.5 15.9 <![CDATA[6.29·10 -2 ]]> Example 7 102.3 36.5 <![CDATA[2.74·10 -2 ]]> Example 8 101.6 26.7 <![CDATA[3.75·10 -2 ]]> Example 9 140.6 46.7 <![CDATA[2.14·10 -2 <!-- 6 -->]]> Comparative Example 1 140.3 60.8 <![CDATA[1.64·10 -2 ]]> Comparative Example 2 137.6 55.4 <![CDATA[1.81·10 -2 ]]> Comparative Example 3 140.4 50.8 <![CDATA[1.97·10 -2 ]]> Comparative Example 4 95.5 210 <![CDATA[4.76·10 -3 ]]> Comparative Example 5 90.1 189 <![CDATA[5.29·10 -3 ]]>

[0080] As shown in Table 2 and Figure 2 It can be seen from the test data shown that the data of Examples 1 to 4 are all better than that of Comparative Example 1, indicating that coating the lithium iron phosphate positive electrode material with a polyaniline coating layer can optimize the charge and discharge performance of the lithium ion battery. This is because polyaniline is a conductive polymer material with electrical conductivity, which can effectively improve the electronic conductivity of the positive electrode material, thereby reducing the internal resistance of the battery and improving the charge and discharge performance of the battery. In addition, the polyaniline in the form of a coating layer may also contribute additional capacity to a certain extent.

[0081] Depend on Figure 3 It can be seen from the EIS test data that after coating with conductive polyaniline, the charging voltage platforms of Examples 1 to 3 are all lower than those of Comparative Example 1, indicating that the positive electrode kinetic performance of Examples 1 to 3 is improved and the polarization is reduced.

[0082] From Table 2 and Figure 4 It can be seen from the test data shown that the data of Examples 7 and 8 are better than those of Comparative Example 4, indicating that coating the sodium iron phosphate positive electrode material with a polyaniline coating layer can optimize the charge and discharge performance of the sodium ion battery. This is because polyaniline is a conductive polymer material with electrical conductivity, which can effectively improve the electronic conductivity of the positive electrode material, thereby reducing the internal resistance of the battery and improving the charge and discharge performance of the battery. In addition, the polyaniline in the form of a coating layer may also contribute additional capacity to a certain extent.

[0083] From the data shown in Table 2, it can be seen that the data of Examples 5 and 6 are better than those of Comparative Examples 2 and 3, indicating that when the amount of ammonium persulfate to aniline is about 1:1, the conductivity of the obtained polyaniline coating layer is optimal.

[0084] The gram capacity data of Example 7 is better than that of Example 8, but the resistivity data is slightly worse, indicating that when the polyaniline coating layer is too thick, although the kinetic performance will be better, the proportion of the positive electrode substrate in the composite material will be reduced, resulting in a decrease in gram capacity.

[0085] Comparing the data of Example 7 with Comparative Examples 4 and 5, Example 7 has the highest gram capacity, while Comparative Example 5 has the lowest gram capacity, indicating that an excessively high content of aniline monomer will affect the gram capacity of the composite positive electrode material.

[0086] The data of Example 9 is better than that of Comparative Example 1, indicating that coating the lithium iron phosphate positive electrode material with a polyaniline coating layer can optimize the charge and discharge performance of the lithium ion battery, and tannic acid as a monomer can also be polymerized into polytannic acid to connect the polyaniline coating layer.

[0087] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite positive electrode material, characterized in that: It comprises a positive electrode material substrate and a polyaniline coating layer coated on the surface of the substrate; The positive electrode material matrix is ​​connected to the polyaniline coating layer via a polymer, and each structural unit in the polymer includes at least two phenolic hydroxyl functional groups.

2. The composite positive electrode material according to claim 1, characterized in that The polymer is one of polydopamine and polytannic acid.

3. The composite positive electrode material according to claim 1, characterized in that: The positive electrode material matrix includes one of a polyanion type sodium ion battery positive electrode material and a lithium ion battery positive electrode material, wherein the polyanion type sodium ion battery positive electrode material includes one of sodium iron phosphate, sodium iron sulfate and sodium vanadium phosphate; the lithium ion battery positive electrode material is one of lithium iron phosphate and lithium iron manganese phosphate.

4. The composite positive electrode material according to claim 1, characterized in that The conductivity of the composite positive electrode material is 10 -4 ~10 -6 S / cm.

5. A method for preparing a composite positive electrode material, characterized in that: The following steps are involved: Step 1: Add polymer monomers to the Tris solution, then add the cathode material matrix, and stir for 3 to 4 hours to obtain a mixed solution A; wherein the pH of the Tris solution is 8 to 9, and the concentration is 0.1 mol / L; Step 2: Filter the mixed solution A, rinse the filter residue with deionized water and anhydrous ethanol, and dry at 70-90° C. for 7-9 hours to obtain the positive electrode material to be coated; Step 3: preparing a coating layer solution, wherein the concentration of aniline is 90-160 mM / L, and the concentration of phytic acid is 9-32 mM / L; preparing a 240-960 mM / L ammonium persulfate aqueous solution; Step 4: adding the positive electrode material to be coated into the coating layer solution, dropping the ammonium persulfate solution, and continuously stirring for 6 to 10 hours to obtain a mixed solution B; Step 5: Filter the mixed solution B, rinse the filter residue with deionized water and anhydrous ethanol, and dry it at 70-90° C. for 6-10 hours to obtain a composite positive electrode material.

6. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In the step 1, the polymer monomer is one of dopamine hydrochloride and tannic acid; and the concentration of the polymer monomer in the mixed solution A is 1.2 mg / mL.

7. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In the step 1, the molar mass ratio of the polymer monomer to the positive electrode material matrix is ​​0.2% to 1.6%.

8. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In the step 3, the molar mass ratio of the aniline to the positive electrode material matrix is ​​3.0% to 5.0%; and / or, in the coating layer solution, the molar mass ratio of the aniline to the phytic acid is 5 to 10:1; And / or, the molar mass ratio of the aniline to the ammonium persulfate is 1:0.5-2.

9. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In the step 4, the stirring condition is an ice bath at a temperature of 0 to 3°C.

10. A positive electrode sheet, comprising a positive electrode material, a conductive agent and a binder, characterized in that: The positive electrode material is the composite positive electrode material according to any one of claims 1 to 4 or a composite positive electrode material prepared by the method for preparing the composite positive electrode material according to any one of claims 5 to 9.